If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -0.80(55) + 136 Multiply -0.80 * 55 y = -44 + 136 Combine like terms: -44 + 136 = 92 y = 92 Solving y = 92 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 92
| 4.3*p=28.81 | | 5n-9=71 | | 5(x+4)=75 | | 6y-7=10y+25 | | y=-0.80(45)+136 | | 7(1y+-2)+8=3(1y+-4)+-2 | | y=-0.80(35)+136 | | -18-6k=6(13k) | | 2x-1=-x+5 | | 15x^3-7x-2= | | x+29=83 | | 16/7=m/21 | | 3x+5=-6 | | 0.2x-1.5=0.1 | | 3a^2+4=0 | | 16-5(3t-4)=8-(-2t+11) | | -7(-5x+7)=-49 | | 4m-4=9m | | 29=17-2x | | 3y+5=y | | 6(-6x-10)=-132 | | 3(x+1)+7(x+1)-6= | | 8x=8x+6 | | 0.5(x+4)-(10x+9)=-77 | | -4(1x+10)=-32 | | 25+15=x | | .33(3x+6)=8x+10 | | -6=-5x+6 | | 9-2+5=260 | | 0.5(x+4)-(10x+9)=-65 | | -.5=4-4.5x | | 4x+(-3)=1 |